O fortalecimento do ecossistema empreendedor a partir dos seus domínios na percepção dos principais atores do ambiente local - Fialho, Camila Borges (2019)
Entrepreneurship has assumed a prominent role both in academia and in the community of practice, as it is a source that enables the improvement of people and institutions that practice entrepreneurship, directly impacting the economic and social development of the community. In order to promote entrepreneurship, Higher Education Institutions (HEIs) become references in this process, as they present conditions to create an environment capable of awakening and enhancing the characteristics and entrepreneurial behavior of students, teachers and all. the actors involved in actions and projects that spill over the boundaries of institutions. In this sense, the organization of actors and all institutions, whether universities or public and private institutions in the vicinity of HEIs, strengthen the environment generating conditions for the promotion of entrepreneurship, which characterizes the entrepreneurial ecosystem, an arrangement defined by Isenberg (2010) by combining different elements such as human resources, support institutions, markets, financial capital, public policies and culture to create an environment conducive to entrepreneurial action. In this logic, this study sought to understand how occurs the strengthening of the entrepreneurial ecosystem from its domains in the perception of the main actors of the local environment. To meet the objectives of the work, a field and qualitative research was conducted, with data collection through interviews with actors who work in the environment in different institutions, who are in positions of relevance to the ecosystem. Data collected in the eight interviews were organized according to the support of NVivo 12 Plus software and content analysis was performed (BARDIN, 2010). The presentation of the results sought to contemplate the six domains of the entrepreneurial ecosystem proposed by Isenberg (2010), as well as the representation of the interviewees' perceptions about the arrangement. Thus, it was realized that there are already in the environment, especially in educational institutions, various practices to foster entrepreneurship, but that still need to be strengthened and combined with other actions outside these institutions. In addition, the actors reported that the ecosystem is not cohesive and that it needs coordination or governance so that actions and projects related to entrepreneurial activity can permeate different structures of society, starting with basic education.